Dechema chemistry data series : activity coefficients at infinite dilution 1 c1 - c9 - Tiegs, D.; Gmehling, J.; Medina, A.; Soares, M.; Bastos, J.; Alessi, P.; Kikic, I. (Dechema Frankfurt, 1986)
part 1
Keywords: coefficients -- infinite dilution